CONTACT DERMATITIS WITH LATEX CONTACT RISK FACTOR IN PT. X - Risti Graharti (Fakultas Kedokteran Universitas Lampung, 2014)
In many industries today, the prevalence of occupational contact dermatitis is increasing with increased use of chemicals in the industry which prevalence reach 67.7%. National Institute of Occupational Safety Hazard estimate the incidence of occupational dermatitis is actually 20-50 times higher than the reported cases. Patients, 49 years old male, with chief complaint of thickened hands accompanied with peeling nails since last 7 years. At first, complaint emerged in the form of itching and burn sensation in both hands, followed by the onset of a round red spots of a pin head and little bit swollen. Eventually, the spots become bubblesfilled with water. Some bubbles contains pus and dried. During these 7 years, the patient's skin thickened and becoming white between the fingers and hands, some sections also appears brown. The patient admitted his fingernails peeled and some parts changed color to brown. The patient was diagnosed with occupational contact dermatitis (irritant and allergic) et causa rubber’s liquid. Patient was given 3x500 mg amoxicillin, dexametason 2x0.5 mg, antihistamine cetirizin 1x10 mg, and betamethasone cream. The non medical therapy was education for wearing protective equipment and avoiding skin contact with rubber or otherchemistry substances, keep personal hygiene by cleaning gloves after use and putting them in a safe place, recognize and preventskin contact with materials which may cause contact dermatitis, reducing severe activity especially in the affected hand. [J Agromed Unila 2014; 1(3):228-231]Keywords: allergic, contact dermatitis, irritant, occupational, rubber